x = 15 + 3y
x² = (15 + y).(15 + y)
x² = 225 + 90 y + 9 y²
225 + 90 y + 10y² = 25
10y² + 90y + 200 = 0
y² + 9y + 20 = 0
(y + 5).(y + 4) = 0
y = - 5 , - 4
x = 0 , 3
(0, - 5) , (3, -4)
2007-02-22 19:15:43
·
answer #1
·
answered by Como 7
·
0⤊
0⤋
The solutions are: (i) x = 3, y = - 4, or (ii) x = 0, y = - 5.
Here's how to find them. From the first equation, x = 15 + 3 y, so substitute that into the second equation:
(15 + 3 y)^2 + y^2 = 25. So:
225 + 90 y + 10 y^2 = 25, that is 10 y^2 +90 y +200 = 0, or
10 (y^2 + 9 y +20) = 0 so that (y + 4)(y + 5) = 0.
The solutions are y = - 4 and x = 15 + 3(- 4) = 15 - 12 = 3,
or y = - 5 and x = 15 + 3(- 5) = 0.
CHECK? Yes, these satisfy the original equations!
Live long and prosper.
P.S. Note that the next response is confused/confusing; you don't "back substitute to determine which of the roots is the correct one to get x." It's NOT a question of only one of the roots being "the correct one to get x." There is a value of x for EACH of the values of y, so you simply back substitute to determine each corresponding x.
2007-02-22 19:12:05
·
answer #2
·
answered by Dr Spock 6
·
1⤊
2⤋
x-3y=15......(1)
x^2+y^2+25...(2)
From eqn 1 ,we get
x=15+3y
Substituting the value of x in eqn 2 we get
(15+3y)^2+y^2=25
=>225+9y^2+90y+y^2=25
=>10y^2+90y+200=0
=>y^2+9y+20=0
=>(y+4)(y+5)=0
Hence y=-4 or- 5
when y=-4,x=15-12=3
when y= -5,x=15-15=0 Hence x= 3,y= -4 and x=0,y= -5 ans
2007-02-22 19:16:35
·
answer #3
·
answered by alpha 7
·
0⤊
0⤋
Substitute 3y + 15 for x in the 2,nd equation to get
(3y + 15)² + y² = 15 multiply it out and simplify to get a quadratic in y. Solve the quadratic and back substitute to determine which of the roots is the correct one to get x.
HTH ☺
Doug
2007-02-22 19:13:22
·
answer #4
·
answered by doug_donaghue 7
·
0⤊
0⤋
start with
x-3y=15
-3y=15-x (subtract x from both sides)
y=(15-x)/-3 (divide by -3, both sides)
so, y=-5+x/3...put this into the second equation
x^2+(-5+x/3)^2=25...solve for x
x^2+(-5+x/3)*(-5+x/3)=25
x^2+25-5x/3-5x/3+x^2/9=25 simplify
x^2-10x/3+x^2/9=0 multiply by 9
9x^2-30x+x^2=0
10x^2-30x=0
x*(10x-30)=0
x=0 and
10x-30=0
x=3
so, x=0 or x=3,
plug these x values in to either equation to find y
i choose the easy one, the first equation
when x=0
0-3y=15
-3y=15
y=-5
when x=3
3-3y=15
-3y=12
y=-4
solved when (x=0 and y=-5) or (x=3 and y=-4)....
Hope this is clear?
2007-02-22 19:48:52
·
answer #5
·
answered by hpage 3
·
0⤊
0⤋
ok x=15+3y
so substitute
(15+3y)^2+y^2=25
225+90y+9y^2=25
9y^2+90y+200=0
and go from there to tired to do the rest sorry
2007-02-22 19:16:43
·
answer #6
·
answered by deep 2
·
0⤊
0⤋